Beginning iOS development with HTML and javascript - Wagner, Richard , 1966- (Wrox beginning guides, 2012)
Web developers with HTML/JS skills will quickly learn to apply them to the iPhone/iPad platformBeginning to intermediate web developers who want to apply their existing HTML/CSS/JS/Ajax skills to the wildly popular iPhone/iPad OS will love this book. In the highly successful Wrox Beginning format, it enables developers who know these core technologies to use what they already know and get up to speed quickly. It introduces iOS development with web technologies, explains how to enable and optimize web sites for the iPhone and iPad, explores user interface design, then moves into animation, spec